PENGARUH PENGGUNAAN BAHASA INDONESIA TERHADAP KEPUASAN PENGGUNA PORTAL LAYANAN MAHASISWA FASILKOM UPN “VETERAN” JATIM - Sholihatin, Endang; Ramadhan, Raihan; Jovian, Abraham Danar; Gabriel, Paskalis Reynaldy Elroy; Triwinanda, Rizqullah Sandya Yossie; Ramadhani, Muhammad Nabil; Bimantoro, Ryan Bagus (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study discusses the influence of the Indonesian language on user satisfaction in the development and use of student service portals at the Faculty of Computer Science at the National Development University "Veteran" East Java. (a) The purpose of this study is to determine the user's understanding and the effectiveness of using the Indonesian language used in the Student Service Portal of the Faculty of Computer Science UPN "Veteran" East Java. (b) To find out whether the use of the Indonesian language increases the interaction between the user and the Service Portal. (c) To find out whether the Indonesian language can minimize user misinformation so that it can affect the level of satisfaction with the Student Service Portal. The research method used was a survey using a questionnaire as a data collection tool. The research sample is UPN "Veteran" East Java Faculty of Computer Science students who actively use the student service portal. (a) The results of the study show that the use of the student service portal can be well understood by the student's family, as evidenced by the data that 99% of students understand the use of the language in the Student Service Portal. (b) Then students who use the Student Service Portal experience an increase in interaction with 98% agreeing because of the use of clear and effective language. (c) Most users report that they are more comfortable interacting with the portal because they use language that is familiar to them and also influences understanding in receiving information. Keyword: Indonesian language, user satisfaction, student service portal